‘Into the wolves’ den: an investigation of predictors of sexism in online games’ - Seo, Young-nam (2022)
Online sexism against female gamers is reportedly common and pervasive, causing serious problems. To help solve these problems, the study identified various predictors of online game sexism, which is hypothesised to predict actual in-game harassment. Different from previous studies, the study approaches the problems from the perspective of perpetrators rather than victims. We proposed a theoretical model that include three groups of predictors: offline sexist beliefs (masculine norms and hostile sexism), game-related factors (perceived territoriality, advancement, and competition), and environmental factors (peer harassment and play time). The model was tested against online survey data collected from a sample of 528 male gamers in South Korea with age range of 14–64 years (M = 34.70, SD = 12.81). The results showed that all the predictors, except competition and play time, were significantly associated with online game sexism, which mediated the relationships between the predictors and online sexual harassment. Perceived territoriality and peer harassment were found to have direct and positive effects on harassment. The findings are expected to contribute to developing more effective measures for preventing the hostility and aggression against female gamers by providing a new and more thorough diagnosis of the underlying causes of the problems.